Carbono acumulado en la biomasa aérea en Terminalia ivorensis A. chev (terminalia) y Gmelina arborea Roxb (melina), en tres cantones del litoral ecuatoriano 2017. - Puentes Galeas, Doris Noemy (2017)
The present study was carried out in three cantons of the Ecuadorian coast, the carbon content was quantified in plantations of Gmelina arborea (melina) and Terminalia ivorensis (terminalia) of nine years of age. The dasometric variables and amount of CO2, was evaluted for the effect applied it was the allometric equations of Clutter 1992, establishing plots of 1000 m2 and a block design completely random. The mean t ha-1 CO2 obtained in melina was 113.58 t ha-1 in the canton Santo Domingo and in the terminalia was 25.39 t ha-1 in the canton Balzar, with significant differences in the variables DBH and basal area between species and species canton. While in biomass and carbon contant significant differences in species were found int the Santo Domingo and Balzar cantons.